Visualizing dopamine released from living cells using a nanoplasmonic probe. Issue 37 (8th September 2015) - Qin, W. W.; Wang, S. P.; Li, J.; Peng, T. H.; Xu, Y.; Wang, K.; Shi, J. Y.; Fan, C. H.; Li, D.
Abstract : We report the development of an ultrasensitive nanoplasmonic probe for discriminative detection and imaging of dopamine released from living cells. Abstract : We report the development of an ultrasensitive nanoplasmonic probe for discriminative detection and imaging of dopamine released from living cells. The sensing mechanism is based on the dopamine-induced seeded-growth of Au nanoparticles (Au NPs) that leads to the shift of the plasmon band. This platform allows for the detection of dopamine with a detection limit down to 0.25 pM within 1 min. This nanoplasmonic assay is further applied to visualize the release of dopamine from living rat pheochromocytoma (PC12) cells under ATP-stimulation with dark-field microscopy (DFM). The DFM results together with real time fluorescence imaging of PC12 cells stained with the Fluo calcium indicator, suggested that ATP stimulated-release of dopamine is concomitant with the Ca 2+ influx, and the influx of Ca 2+ is through ATP-activated channels instead of the voltage-gated Ca 2+ channel (VGC).